The Effect of Cash Management and Operational Cost Control on Business Profit: Evidence from Agung Trading Business in Tanjung Menang Jarai Village - Sholikhatamara Sholikhatamara; Elvera Elvera; Ruaman Yudianto (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The purpose of this study is to determine and describe the Effect of Cash Management and Operational Cost Control on Business Profit at